China’s Experience And Uzbekistan’s Wto Accession Process: Opportunities In Trade And Economic Relations - Abdullayev, Akhrorjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article analyzes China’s experience of joining the WTO and its economic results, considers the opportunities and problems of this process for Uzbekistan. The current state of trade and economic cooperation with China and its prospects within the WTO are highlighted. The need for supporting local manufacturers, diversifying exports and technological innovation is substantiated.